Diagnostic Application of B-scan Ultrasonography (Medical Forum Monthly, 2023)
Objective: To investigate the role of B-scan ultrasonography in diagnosing ocular disorders.Study Design: A retrospective studyPlace and Duration of Study: This study was conducted at the Saidu Group of Teaching Hospital from September 2022 to September 2023.Methods: A retrospective study was conducted on a total of 100 patients with media opacity due to cataracts, diabetes, corneal dystrophy, trauma, leukocoria, hypertension or Eale's disease. B-scan ultrasonography, systemic exams, optical acuity tests, and other in-depth diagnostics were conducted.Results: Patients ranged in age from 6 months to 80 years, with the highest prevalence of ocular disorders observed in the 11 to 20-year age group (45%). Various ocular pathologies were identified, including corneal pathologies (5%), mature cataracts (9%), vitreous hemorrhage (7%), retinal detachment (15%), tractional retinal detachment (12%), retinoblastoma (3%), and others. Notably, 44 patients (44%) had multiple concurrent pathologies. Traumatic injuries, particularly in males aged 11 to 30, were a leading cause of ocular pathology. B-scan ultrasonography was critical in trauma assessment, cataract surgery planning, vitreous hemorrhage management, detecting intraocular foreign bodies, and diagnosing post-traumatic endophthalmitis.Conclusion: B-scan ultrasonography is indispensable in diagnosing a wide spectrum of ocular disorders, especially in cases of media opacity. This study underscores its significance in trauma evaluation, cataract surgery, vitreous hemorrhage management, foreign body detection, and post-traumatic endophthalmitis diagnosis.